The ways of handling stress and the attachment forms to parents of university students - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
The aim of the study was to determine the ways of handling stress and attachment forms to parents for university students. The content of this research, which has been done in a descriptive manner, covers the 1st, 2nd, and 3rd year students of the department of Nursing in the Faculty of Health Sciences and Faculty of Education (N=795) of a state university in the education year of 2010-2011. For this research, no sampling method has been chosen but the whole environment taken as samples. However, only 711 of the students agreed to participate to the research. Upon receiving the approval from the institutions, the students were told the aim of the research and forms collected after class by the researchers. The tools to collect data; a form including 22 questions, which prepared by the researchers, a scale for Parental Attachment Style Instrument-(PASI; form of mother alpha=.87, form of father=.89), and Ways of Coping Inventory. Ways of Coping Inventory: It has been developed to measure the ways individuals use to handle stress by Folkman and Lazarus(1980). The Turkish adaptation of it has been done by Sahin and Durak (1995). The data have been evaluated through descriptive statistics, chi-sqare, t test and correlation analysis. 36.4% of the students study at the department of Nursing and 63.6% of them study at the department of Teaching Training. Through PASI, it has been measured that the average for caring mother at low level is 18.71 while the average for controlling/ over protecting mother is 12.63, meanwhile average for caring father is 18.62 but the average for controlling/overprotecting father is 13.67. When we look at the ways to handle stress of the sample group, it has been concluded that subjects use the ways of seeking the most social support, confident approach towards them, optimistic approach, insecure/desperate approach and obedient approach in this order.
Keywords: University students; attachment styles; coping; ADULT ATTACHMENT; ALEXITHYMIA; ADOLESCENTS; DEPRESSION; DISTRESS; STYLES